FORMATION OF LEARNING IN STUDENTS - Sultonov Ravshanbek Rustamovich; Isomaddinova Umida Mamurjonovna; O. Karimova (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the formation of learning motives of students at school the development of thinking, the development of thinking, the formation of knowledge, and skills.